2016
DOI: 10.1016/j.hal.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sodium channel mutations in Makah tribal members of the U.S. Pacific Northwest as a potential mechanism of resistance to paralytic shellfish poisoning

Abstract: The Makah Tribe of Neah Bay, Washington, has historically relied on the subsistence harvest of coastal seafood, including shellfish, which remains an important cultural and ceremonial resource. Tribal legend describes visitors from other tribes that died from eating shellfish collected on Makah lands. These deaths were believed to be caused by paralytic shellfish poisoning, a human illness caused by ingestion of shellfish contaminated with saxitoxins, which are produced by toxin-producing marine dinoflagellate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In high-income countries, consumers’ perception of the safety of seafood has led to a reduction in demand for shellfish, and this change has had severe economic consequences for the shellfish industry [ 512 ]. The lack of diagnostic tools and treatment options for HAB-related illnesses leads to increased psychological stress in fishing communities [ 513 514 ].…”
Section: Impacts Of Ocean Pollution On Human Healthmentioning
confidence: 99%
“…In high-income countries, consumers’ perception of the safety of seafood has led to a reduction in demand for shellfish, and this change has had severe economic consequences for the shellfish industry [ 512 ]. The lack of diagnostic tools and treatment options for HAB-related illnesses leads to increased psychological stress in fishing communities [ 513 514 ].…”
Section: Impacts Of Ocean Pollution On Human Healthmentioning
confidence: 99%
“…Nearly 70% of households participate in shellfish harvest activities [ 32 ]. Members of the Makah Tribe tell the story of potlatches (tribal ceremonial feasts) where visitors would come from over the mountains to share in the seafood bounty [ 32 , 33 ]. These stories suggest that the visitors became ill from consuming shellfish which contained toxins, while the Makah, who habitually rely on shellfish in their diet, did not.…”
Section: History Of Us Ocean and Human Health Program In The Pacifmentioning
confidence: 99%
“…These traditional stories provided inspiration to further our understanding of genetic resistance to toxins in shellfish that consume toxic algae [ 34 ], leading to a collaboration with the Makah Tribe to understand whether people, such as the Makah, who consumed shellfish also demonstrated resistance to toxins. This study showed that, in contrast to shellfish which can feed on and accumulate toxic algae and survive [ 32 , 34 ], tribal members do not appear to be resistant to toxins in their shellfish food [ 33 ]. This knowledge informed an optimal strategy for human health protection and outreach associated with HABs and their toxins.…”
Section: History Of Us Ocean and Human Health Program In The Pacifmentioning
confidence: 99%